The Beneficial Role of Some Bone Markers in Evaluating Women with Osteoporosis under Different Therapeutic Regimens - A. Abbass, Shaima; H. Ali, Shatha (Iraqi Journal of Pharmaceutical Sciences, 2017)
Osteoporosis is a systemic disease of the skeleton, characterized by low bone mass and alteration in the micro-architecture of the bone tissue that lead to an increase in brittleness with the ensuing predisposition to bone fracture. Global statistics shows that women are more exposed to this disease than men and in particular at menopause. This study was designed to evaluate the use of some bone markers: serum osteocalcin (Ost), alkaline phosphatase (ALP), as bone formation markers, also parathyroid hormone (PTH), calcium and inorganic phosphate level, for the assessment of patients with osteoporosis and to evaluate their role in monitoring of several types of therapeutic interventions (such as bisphosphonates, hormonal replacement therapy, and Ca and vit.D) in postmenopausal women.This study comprised of 36 women (age 51.67Â±5.14 years) those diagnosed to have osteoporosis, to be allocated randomly into three groups according to the type of therapy to be given as; group A: received bisphosphonates (sodium alendronate 10mg/day) for twelve weeks (N=12). group B: treated with hormonal replacement therapy (conjugated estrogen 0.625mg/day) for twelve weeks (N=12). group C: received Ca and vit. D (Ca1500mg/day and cholecalciferol 1000IU/day) for twelve weeks(N=12). In addition to 15 perimenopausal healthy women to serve as a control group (age 51.13Â±7.62 years).The studied parameters were measured in serum obtained before starting treatment and after 12 weeks of therapy. Result indicated that the baseline values of both serum Ost and ALP were significantly higher in postmenopausal patients as compared to controls and serum Ost showed a significant reduction after treatment with alendronate compared to those treated with either HRT or Ca and vit. D.From this study we recommend estimating the baseline bone markers (Ost and ALP) status for newly diagnosed osteoporotic patients to be used as a guide for deciding the initial therapeutic intervention, and detection of non responder instead of waiting until patients develop further fracture while they are on therapy. Key words: Osteoporosis, Postmenopause, Osteocalcin, Alendronate